Variation of hepatic glucuronidation: Novel functional polymorphisms of the UDP-glucuronosyltransferase UGT1A4 - Ursula Ehmer; Arndt Vogel; Jan Karl Schütte; B Krone; Michael P. Manns; Christian P. Strassburg (2004)
UDP-glucuronosyltransferases are a family of drug metabolizing enzymes contributing to hepatic drug metabolism and protection against environmental toxins. The aim of this study was to identify polymorphisms at the human UGT1A gene locus and to characterize their function and potential association with hepatocellular carcinoma (HCC). Genomic DNA from the blood of 363 subjects (128 patients with HCC, 235 blood donors) was analyzed for polymorphisms of the UGT1A3, UGT1A4, UGT1A8, UGT1A9, UGT1A10 genes using polymerase chain reaction, sequencing analysis. Recombinant variant UGT protein was analyzed by activity assays. In the UGT1A8 gene an A173G variant and a conserved G to A exchange at position 765 were detected in 25% and 15%. UGT1A9 exhibited two variants C3Y and M33T in 1% and 3%. UGT1A10 exhibited conserved nucleotide exchanges (128 G-->A and 696 C-->T) in 2% and 13%. In the UGT1A3 gene a W11R, a V47A variant, and a conserved G to A exchange at position 81 with an incidence of 65%, 58%, and 65%, respectively, were identified. UGT1A4 exhibited a P24T and an L48V variant in 8% and 9%. UGT1A SNPs were not associated with HCC. UGT1A4 P24T and L48V exhibited reduced glucuronidation activities: beta-naphthylamine 30% and 50%, and dihydrotestosterone 50% and 0%, respectively. In conclusion, the high prevalence of SNPs throughout the human UGT1A gene locus illustrates a genetic basis of interindividual variations of hepatic metabolism. Two polymorphisms of the hepatic UGT1A4 protein show a differential metabolic activity toward mutagenic amines and endogenous steroids, altering hepatic metabolism and detoxification.